Optimalisasi Rute Distribusi Produk PVC Guna Meminimasi Biaya Transportasi pada PT. Tjakrindo Mas Gresik - Muchamad Sainul Abidin; Herlina Herlina (LPPM Universitas Pahlawan Tuanku Tambusai, 2026)
Operational cost efficiency, particularly in transportation, is a critical factor in supporting the performance of a company's distribution system. PT Tjakrindo MAS Gresik faces challenges regarding suboptimal distribution routes, underutilized vehicle capacity, and high transportation costs caused by inefficient travel distances. The current distribution system is based solely on regional division without considering the integration between distributor demand and vehicle capacity. This lack of integration leads to empty cargo space, increased operational time, and a total distribution travel distance of 5,130.8 km. This study aims to design more optimal distribution routes and minimize transportation costs using the Capacitated Vehicle Routing Problem (CVRP) method with a Mixed Integer Linear Programming (MILP) approach, solved using LINGO software. The data utilized includes distances between locations, distributor demands, vehicle capacities, fleet size, and transportation costs. The results of this study are expected to yield more efficient distribution routes through reduced travel distance, increased vehicle utilization, and decreased transportation costs compared to the existing distribution system.